2022
DOI: 10.1186/s12884-022-04473-w
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mode of delivery on health-related quality-of-life in mothers: a systematic review and meta-analysis

Abstract: Background Previous research is inconclusive on the effects of mode of delivery on maternal health-related quality-of-life (HRQoL). We conducted a systematic review and meta-analysis to assess the current evidence for associations between mode of delivery and postpartum health-related quality-of-life. Methods Electronic databases MEDLINE ALL (OVID), Web of Science, The Cochrane Library, CINAHL and EMBASE (OVID) were searched for English written art… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 65 publications
1
7
0
Order By: Relevance
“…Also, a meta-analysis by Evans et al . 37 found a significantly higher QoL in women with vaginal delivery. However, similar to Torkan et al .…”
Section: Discussionmentioning
confidence: 88%
“…Also, a meta-analysis by Evans et al . 37 found a significantly higher QoL in women with vaginal delivery. However, similar to Torkan et al .…”
Section: Discussionmentioning
confidence: 88%
“…Whereas a number of studies are available on the long-term consequences in cases where a surgical birth is associated with higher fatigue, no studies are available specifically covering the early postpartum period in this respect [ 54 ]. Therefore, while, in general, a spontaneous birth is more easily tolerated than a CS birth, this does not necessarily apply to older women in the early postpartum period [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that women who gave birth vaginally had a significantly higher postpartum quality of life than those who gave birth by cesarean section. The association was statistically significant for the physical component, physical role, physical function, vitality, and social function 7 .…”
Section: Introductionmentioning
confidence: 88%